Producing yam (Dioscorea) seeds through controlled crosses - Mignouna, Hodeba D.; Abang, Mathew M.; Asiedu, Robert; Geeta, R. (Cold Spring Harbor Laboratory, 2009)
This protocol describes how to produce yam (Dioscorea) seeds through controlled pollination of flowers on female plants. Pollination by flower thrips takes place naturally in normal yam-growing environments in the presence of flowering male and female genotypes, although it is not efficient. This protocol leads to the production of hybrid seeds of known parentage for genetic studies and use in breeding programs.